Improper sharp disposal practices among diabetes patients in home care settings: Need for concern? - Anindo Majumdar; Jayaprakash Sahoo; Gautam Roy; Sadishkumar Kamalanathan (Indian Journal of Endocrinology and Metabolism, 2015)
In the recent years, outbreaks of blood-borne infections have been reported from assisted living facilities, which were traced back to improper blood glucose monitoring practices. Needle-stick injuries have been implicated in many such cases. This directly raises concerns over sharp disposal practices of diabetic patients self-managing their condition in home care settings. With India being home to a huge diabetic population, this issue, if neglected, can cause substantial damage to the health of the population and a marked economic loss. This article discusses the sharp disposal practices prevalent among diabetes patients, the importance of proper sharp disposal, barriers to safe disposal of sharps, and the options available for doing the same. For adopting an environmentally safe wholesome approach, disposal of plastics generated as a result of diabetes self-care at home is important as well. The article also looks at the possible long-term solutions to these issues that are sustainable in an Indian context.